Cultura e polissistema literário nas traduções para o inglês de Relato de um certo oriente de Milton Hatoum - Silva, Fernanda Lair Zuconelli Machado da (2023)
This study aims to analyze the cultural elements in the English translations of Milton Hatoum's Relato de um certo Oriente, considering the relevant aspects of the positioning of the translated works in their polysystems, and also the perspective of Cultural Studies and Translation Studies. To develop this goal, the cultural marks represented in the text were explored with a focus on the protagonist narrator's search for identity through the re-signification of cultural images of the city of Manaus. Next, we investigated the reception of the translated works in their literary polysystems, the first target text being The tree of the Seventh Heaven, which was translated by Ellen Watson and published in 1994 in the United States. The second target text analyzed was the revision by John Gledson and published in 2004 in the United Kingdom, entitled Tale of a Certain Orient. Subsequently, the analysis was performed in order to verify the forms of transposition of the cultural and linguistic aspects of the lexicon referring to the city spaces in the sixth chapter, narrated by the protagonist. The theoretical contribution comprises the authors of Translation Studies, such as Itamar Even-Zohar (1990; 2013), Gideon Toury (2012), Lawrence Venuti (2019), and Rafael Lanzetti et al. (2009). At the end of the analyses, the maintenance of style and syntactic structure was found in certain decisions by the translators. The technical procedures of domesticating translation were mostly employed, culminating in more fluent texts for the target systems, however, distant from the source text. It was observed that some of the translators' decisions erased or modified meaning effects belonging to the source cultural system, regarding the thematic axis of the city of Manaus space represented in the text.